Li-Fraumeni syndrome - Xue-bin ZHANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2018)
Objective To investigate the clinicopathological features of Li - Fraumeni syndrome (LFS) manifested as glioblastoma. Methods and Results A 33 - year -old female patient presented hyperspasmia of left extremities. Head MRI showed space - occupying lesion on the right fronto - parietal junction, and contrast - enhanced scanning revealed "garland" enhancement of the lesion. The patient underwent surgical resection. During the operation, an oval tumor was visible after the right parietal cortex was cut open for 2.50 cm, which was about 5 cm × 4 cm × 3 cm in size. The tumor was soft and purple, with clear boundary and rich blood supply, and was totally removed through piecemeal resection. Microscopic examination found obvious dysplasia of glial cells, spindle shape in some areas, and a large number of giant tumor cells. Immunohistochemical staining showed that the tumor cells expressed glial fibrillary acidic protein (GFAP) in cytoplasm and P53 protein in nuclei. Ki-67 labeling index was 25%. Reticular fiber staining was negative. Molecular pathological examination did not detect isocitrate dehydrogenase 1/2 (IDH1/2) gene exon 4 mutation, telomerase reverse transcriptase (TERT) promoter mutation, or methylation of O6-methylguanine-DNA methyltransferase (MGMT). Fluorescence in situ hybridization (FISH) analysis did not reveal codeletion of 1p/19q. The integrated diagnosis was (right parietal) glioblastoma, IDH - wild type (WHO grade Ⅳ). The patient was hospitalized for 15 d and died in 2016. Previous family medical history showed her older sister suffered from right breast cancer, her father died of gastic cancer, her grandmother died of breast cancer, her uncles died of lung cancer and hematopoietic system tumor. Samples from the patient's glioblastoma and right mammary gland invasive duct carcinoma were collected for TP53 gene detection, but no mutation was found. Further, whole exome sequencing (WES) on the patient's freezing blood samples showed TP53 gene c.1009C > T (p.Arg337Cys) pathogenic heterozygous mutation (missense mutation). Combined with the family cancer history, a clinical diagnosis of the patient was Li-Fraumeni syndrome, and her family was Li-Fraumeni syndrome pedigree. Conclusions Li-Fraumeni syndrome is a hereditary tumor syndrome with autosomal dominant inheritance, characterized by high risk of breast cancer, bone and soft tissue sarcoma, brain tumor and adrenocortical cancer, and TP53 gene is the most common gene associated with Li-Fraumeni syndrome.